Quasinormal modes for the Vaidya metric in asymptotically anti-de Sitter spacetime - Lin, Kai; Liu, Yunqi; Qian, Wei-Liang [UNESP]; Wang, Bin; Abdalla, Elcio (American Physical Society (APS), 2019)
In this work, we present a numerical scheme to study the quasinormal modes of the time-dependent Vaidya black hole metric in asymptotically anti-de Sitter spacetime. The proposed algorithm is primarily based on a generalized matrix method for quasinormal modes. The main feature of the present approach is that the quasinormal frequency, as a function of time, is obtained by a generalized secular equation and therefore a satisfactory degree of precision is achieved. The implications of the results are discussed.